Virtual reality development and simulation of BMI nozzle inspection system for use during regular refueling outage of APR1400 family of reactors. (June 2018) - Abdallah, Khaled Atya Ahmed; Namgung, Ihn
Highlights: RV BMI nozzle is J-groove welded from inside. This location has shown leaks in some NPPs in the past such as STP in 2003 and Palo Verde-3 in 2013. Development of inspection system for RV BMI nozzle without removal of reactor internals is studied and the operation of the inspection system was simulated to prove the validity of the system. Structural analysis of the design was performed and had shown the structural soundness of the developed system. With the RV BMI nozzle inspection system, inspection of RPV BMI nozzle during regular refueling outage become possible without removing reactor internals. This allows finding defect at an early stage of defect formation and prevent RV crack caused by the BMI nozzle leak. Abstract: Reactor vessel bottom mount instrumentation nozzle is J-groove welded to reactor vessel inside. This location has shown leaks in some NPPs in the past such as pinhole leaks at the South Texas Project in 2003 and a similar trace of leak at Palo Verde Unit 3 in 2013. Inspection of reactor vessel bottom mounted instrumentation nozzle weld crack requires removal of reactor internals in the case of APR1400 family of reactors without special tools. In Korea, the removal of reactor internals is prohibited during regular refueling outage following regulatory guidelines, hence the inspection of defects in reactor vessel bottom mounted instrumentation nozzle from inside of reactor vessel has not been performed during a regular refueling outage. In this study, a remote weld inspection system for reactor vessel bottom mounted instrumentation nozzles is developed in a virtual environment, and the operation of the inspection system was simulated to prove the validity of the system. The aim of the reactor vessel bottom mounted instrumentation nozzle inspection system was to inspect reactor vessel bottom mounted instrumentation nozzle during regular refueling outage without removing RI. This allows inspection of reactor vessel bottom mounted instrumentation nozzle weld for every refueling outage and allows finding defect at an early stage of defect formation and prevent reactor vessel crack caused by primary water stress corrosion cracking which lead to the bottom mounted instrumentation nozzle leak.